107k views
4 votes
Please help with the second question below.

The answers are A., B., D., and E.

Please help with the second question below. The answers are A., B., D., and E.-example-1
User Sara Brown
by
6.0k points

1 Answer

1 vote

Answer:

The answers A,B,D and E are verified.

Step-by-step explanation:

We have equation, x⁴ - 3 x² + 2 = 0

Substituting y = x²

So equation is y²- 3 y+ 2 = 0

=> (y-1)(y-2) = 0

y = 1 or y = 2

So we have x² = 1 or x² = 2

=> x = 1 , x = -1 ,
x=√(2) or
x=-√(2)

So the answers are A,B,D and E.

User Bob Stein
by
6.2k points